Electrical impedance tomography in calves with bovine respiratory disease: correlations with clinical and blood gas findings - Bleul, Ulrich; Kluser, Fabienne; Waldmann, Andreas; Gerspach, Christian (Frontiers in Veterinary Science, 2025)
Bovine respiratory disease (BRD) is a multifactorial global problem associated with long-term deleterious effects on the well-being of calves and marked financial losses. Prompt diagnosis of BRD, monitoring the success of treatment, and providing an accurate prognosis remain challenging because current methods for stall-side diagnosis are inadequate. To improve diagnosis in addition to clinical and morphological findings and gain insight into the respiratory dynamics of BRD, thoracic electrical impedance tomography (EIT) was used to evaluate calves with BRD (Group D; n = 42) and healthy calves (Group H; n = 13). Thoracic EIT is a non-invasive method of quantifying differences in impedance changes between various lung regions and impedance changes over time. A belt with 32 equidistantly mounted electrodes was placed around the thorax of non-sedated calves of both groups to measure impedance changes during respiration. The results were compared with the clinical findings and the California BRD scores. Compared with group H, Group D had decreased ventilation in the ventral lung regions (p = 0.05); ventilation shifted to the left lung lobes in calves with marked auscultatory changes (p = 0.013). In addition, the quartile ventilation ratio on inspiration (VQRi), used to quantify changes in impedance during inspiration, differed significantly between the two groups (p = 0.0039). Of all the EIT parameters, VQRi correlated most closely with paO2 and the A-a-gradient and was significantly lower in group D than in group H (p = 0.061). The results of EIT revealed differences in the inspiratory dynamics of clinically healthy and ill calves and correlated with the clinical and blood gas findings. Thus, EIT can be used alone or together with other diagnostic tools to identify and monitor BRD in calves.